Double helical order and functional properties of acid-hydrolyzed maize starches with different amylose content. (April 2020) - Soler, Adrian; Valenzuela-Díaz, Erendira D.; Velazquez, Gonzalo; Huerta-Ruelas, Jorge A.; Morales-Sanchez, Eduardo; Hernandez-Gama, Regina; Mendez-Montealvo, Guadalupe
Abstract: Two maize starches (Normal and Hylon VII) were hydrolyzed using HCL for 15 days at room temperature. The water holding capacity -WHC and oil holding capacity- OHC were evaluated to describe the changes during the reorganization of hydrolyzed material. The structure was assessed using differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR). A hydrolysis degree of 20% was reached with a complete granular structure disruption. During acid hydrolysis, the rearrangement of decoupled double helices favored the order degree. The hydrolysis of the amorphous region decreased the enthalpy of gelatinization. This effect was more noticeable in the normal starch. The changes promoted during the hydrolysis favored the reorganization of the network resulting in high values in WHC and OHC for both starches. The acid-treated starches obtained could be used as fillers, employing these materials with induced crystalline regions. Graphical abstract: Image 1 Highlights: At 20% of hydrolysis degree a complete granular structure disruption was reached. The rearrangement of decoupled double helices favored the order degree. The network reorganization resulted in high values of WHC and OHC for MS and HVIIS. The acid-treated starches could be used as a filler material.